The contested place of religion in family law / edited by Robin Fretwell Wilson. - Wilson, Robin Fretwell (Cambridge University Press, 2018)
Like many beliefs, religious views matter across an individual's life and the life cycle of a family - from birth to marriage, through child-rearing, and, eventually, death. This volume examines clashes over religious liberty within the personal realm of the family. Against swirling religious beliefs, secular values, and legal regulation, this volume offers a forward-looking examination of tensions between religious freedom and the state's protective function. Contributors unpack some of the Court's recent decisions and explain how they set the stage for ongoing disputes. They evaluate religious claims around birth control, circumcision, modesty, religious education, marriage, polygamy, shared parenting, corporal punishment, faith healing, divorce, and the end of life. Authors span legislators, attorneys, academics, journalists, ministers, physicians, child advocates, and representatives of minority faiths. The Contested Place of Religion in Family Law begins an overdue conversation on questions dividing the nation.